2019
DOI: 10.1155/2019/2425904
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation Research of Smooth Wall Blasting Using the Timing Sequence Control Method under Different Primary Blast Hole Shapes

Abstract: To make sure the integrity and stability of surrounding rock structure during blasting excavation of important structural planes in deep underground caverns, two kinds of fine blasting methods, timing sequence control fracture blasting network and notch blast hole, are innovatively combined and the formation of cracks between smooth blasting holes with different delay initiation and different shapes of primary blast holes (PBHs) are compared and analyzed. The results show that when the delay initiation time be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…In this simulation, the explosive and air were defined as ALE grids, and the Lagrange algorithm was performed for the rock mass and stemming. Using the keyword * CONSTRAINED_LAGRANGE_IN_SOLID, the fluidsolid coupling algorithm was defined to realize the transfer of blasting energy from the detonation products to the rock mass and stemming [38,39]. Nonreflecting boundaries were applied to the model surface in addition to the working face to reduce the influence of stress wave reflections on the simulation results [40,41].…”
Section: Numerical Modelmentioning
confidence: 99%
“…In this simulation, the explosive and air were defined as ALE grids, and the Lagrange algorithm was performed for the rock mass and stemming. Using the keyword * CONSTRAINED_LAGRANGE_IN_SOLID, the fluidsolid coupling algorithm was defined to realize the transfer of blasting energy from the detonation products to the rock mass and stemming [38,39]. Nonreflecting boundaries were applied to the model surface in addition to the working face to reduce the influence of stress wave reflections on the simulation results [40,41].…”
Section: Numerical Modelmentioning
confidence: 99%
“…Regarding the crack damage evolution of an empty hole in the blasting groove area, Meng et al (2020) established the rock mass damage tension constitutive model plate with LS-DYNA, studied the rock mass damage caused by the empty hole effect, and concluded that the existence of the empty hole significantly improved the tensile stress and stress concentration coefficient near the empty hole. In this work, the stress wave propagation during cut blasting was analyzed, and through dynamic blasting experiments, the bastings in specimens with circular, square and cut holes were analyzed and compared, and the propagation of the corresponding stress waves and explosion cracks were observed (Li et al 2019). Sun et al (2019) determined that the hole arrangement will affect the rock breaking effect of the groove area and determined the most suitable empty hole spacing.…”
Section: Introductionmentioning
confidence: 99%
“…Since it takes approximately twice as long to drill a notched hole than a round hole, the construction process of blast excavating the underground powerhouse will be affected. Based on the TSC fracture blasting excavation method proposed by Li 48 , only PBHs are notched in the rock mass model with filled joints; the distance between adjacent boreholes is taken as approximately 19 times the diameter of the boreholes, i.e., 800 mm; the delayed initiation time between PBH and TBH is taken as 1 ms. To compare and analyse the effects of the round target borehole with and without stress concentration effects on the crack propagation, the method in Fig. 10 is used to connect the smooth blasting borehole circuit.…”
Section: Numerical Analysis Of the Tsc Fracture Blasting Methods For A Pbh Notchmentioning
confidence: 99%